Pulmonary hypertension in adults with congenital heart defects (ACHDs)—in light of the 2022 ESC PAH guidelines—part I: definition, epidemiology, classification, diagnostics, genetics, risk stratification and follow-up, gender aspects - Kaemmerer, Harald; Diller, Gerhard Paul; Dähnert, Ingo; Achenbach, Stephan; Eichstaedt, Christina A.; Eicken, Andreas; Freiberger, Annika; Freilinger, Sebastian; Geiger, Ralf; Gorenflo, Matthias; Grünig, Ekkehard; Hager, Alfred; et al. (Cardiovascular Diagnosis and Therapy, 2024)
The number of adults with congenital heart defects (ACHDs) is steadily increasing and is about 360,000 in Germany. Congenital heart defect (CHD) is often associated with pulmonary hypertension (PH), which sometimes develops early in untreated CHD. Despite timely treatment of CHD, PH not infrequently persists, redevelops in older age, and is associated with significant morbidity and lethality. The revised European Society of Cardiology (ESC)/European Respiratory Society (ERS) 2022 guidelines for the diagnosis and treatment of PH represent a significant contribution to the optimized care of those affected. However, the topic of “adults with congenital heart defects” is treated only relatively superficially in this context. In the present article, part I, therefore, this topic is commented on in detail from the perspective of congenital cardiology with a special focus on definition, epidemiology, classification, diagnostics, genetics, risk stratification and follow-up and gender aspects of PH in ACHDs. This paper consists of two parts. Part II will provide comments on the topics of supportive therapy, special situations like pregnancy, contraception, and non-cardiac surgery, targeted pharmacotherapy, organ transplantation, special management like shunt lesion, left ventricular disease, and univentricular hearts, interventions, intensive care, ACHDs follow-up and future perspective on PH in ACHDs. By examining these aspects in detail, this article aims to fill the gaps in the existing guidelines and provide a more thorough understanding from the perspective of congenital cardiology.
CRIS-Team Scopus Importer:2024-11-08
Keywords: congenital heart disease; Eisenmenger syndrome; Pulmonary arterial hypertension (PAH)